Gradual Collective Wage Bargaining - Sabien Dobbelaere; Roland Iwan Luttens (Institute for the Study of Labor (IZA), 2016)
This paper presents an alternative implementation of firm-level collective wage bargaining, where bargaining proceeds as a finite sequence of sessions between a firm and a union of variable size. We investigate the impact of such a 'gradual' union on the wage-employment contract in an economy with concave production. In a static framework, the resulting equilibrium is equivalent to the efficient bargaining outcome. In a dynamic framework with search frictions, we demonstrate that gradual collective wage bargaining coincides with all-or-nothing bargaining when bargaining takes place in fictitious time before production.
Keywords: J30; J41; J51; 330; collective bargaining; gradual union; firm; search frictions; employment-at-will